An uncommon inborn error of immunity in an adolescent with Hodgkin lymphoma and bronchiectasis - Sangeetha Ramdas; Sidharth Totadri; Priyanka Medhi; Elanthenral Sigamani; Arun Kumar Arunachalam; Leni Grace Mathew (Elsevier, 2024)
Background: Individuals with inborn errors of immunity (IEI) have an increased risk of developing malignancies compared to their peers. We report a case of Hodgkin lymphoma in an adolescent with CD27 deficiency. Case report: A 15-year-old girl presented with cervical swelling and breathlessness for 3 days. Her past history was remarkable, with a history of recurrent respiratory infections. On examination, she had grade 2 clubbing, bilateral cervical lymphadenopathy, hepatosplenomegaly, and bilateral coarse crepitations. Biopsy showed overlapping immunomorphological features of classic Hodgkin lymphoma (HL), with features intermediate between diffuse large B-cell lymphoma and HL. A staging PET-CT revealed a stage III disease and bronchiectatic changes in bilateral lungs. The serum immunoglobulin levels showed hypogammaglobulinemia. Next generation sequencing demonstrated a homozygous missense variant in the CD27 gene (c.319C>T; p.Arg107Cys). She was treated with ABVD/COPDac chemotherapy along with supportive care. She is currently 16 months post-treatment. Conclusion: CD 27 deficiency is a rare IEI with a common variable immunodeficiency phenotype and a high propensity to develop lymphomas. Clinical suspicion, early detection, and management are warranted to prevent complications and mortality.